META-ANALISIS: LITERASI DIGITAL PADA PEMBELAJARAN SMA - Risqah Amaliah Kasman; Sape, Herwandi (Jurnal Pendidikan dan Pembelajaran, 2023)
Digital literacy have an important role in the learning process. Several articles state that the use of digital literacy can improve the quality and learning outcomes at high school level. To investigate the extent of the impact of digital literacy on learning, a meta-analysis was carried out on articles discussing digital literacy in the learning context and published in national journals with a SINTA index of 1-6. This research uses a meta-analysis design with a sample of 16 digital literacy articles on learning that meet the sample selection criteria. Research data was obtained from the analysis of these articles, and the results were analyzed by considering the effect size of each article based on the t-test. Research findings show that the average effect size value is 0.373, indicating that digital literacy has a significant impact on learning in the large effect category.